Symmetry-dependent electron-electron interaction in coherent tunnel junctions resolved by measurements of zero-bias anomaly - COEY, JOHN (My University, 2014)
We provide conclusive experimental evidence that zero-bias anomaly in the differential resistance of magnetic tunnel junctions is due to electron-electron interaction (EEI), clarifying a longstanding issue. The magnon effect that caused confusion is now excluded by measuring at low temperatures down to 0.2 K and with reduced ac measurement voltages down to 0.06 mV. The normalized change of conductance is proportional to ln(eV/kBT), consistent with the Altshuler-Aronov theory of tunneling that describes the reduction of density of states due to EEI, but inconsistent with magnetic impurity scattering. The slope of the ln(eV/kBT) dependence is symmetry dependent: the slopes for parallel and antiparallel states are different for coherent tunnel junctions with symmetry filtering, while nearly the same for those without symmetry filtering (amorphous barriers). This observation may be helpful for verifying symmetry-preserved filtering in search of new coherent tunneling junctions, and for probing and separating electron Bloch states of different symmetries in other correlated systems.
PUBLISHED
Keywords: amorphous barriers; amorphous barriers